A scandalous match for the Marquess - Merrill, Christine (Harlequin historicals., 2024)
Author Felicity Morgan has been banished to the English countryside by her family, but her exile has a silver lining--spending time with the widower Martin Howell, Marquess of Woodley, leading them both to reconsider their separate, future plans to remain unwed no matter the consequences.